Enterolobin induces rat paw oedema independently of PAF-acether - Castro Faria Neto,H. C. (1991)
The potential participation of PAF-acether (PAF) on the paw oedema triggered by enterolobin was investigated. Intraplantar injections of enterolobin )5-20 µg/paw) yielded a dose response curve for edema which appeared after 30 min, peaked in the interval between 2-4 h and faded after 24h. The pre-treatment with BN 52021, but not with other PAF antagonists such as PCA 4248 or WEB 2086, significantly blocked enterolobin-induced oedema. To clarify better the discrepant results obtained with the PAF antagonists, desensitization to PAF was performed. The oedema triggered by enterolobin was not modified in paf desensitized animals. It was concluded that the paw inflammation induced by enterolobin does not require PAF mechanism.